Late-Onset Bleb-Related Endophthalmitis Caused by Moraxella nonliquefaciens: A Case Report - Su-Chin Shen; Kuan-Jen Chen (MDPI AG, 2023)
Moraxella species are Gram-negative coccobacilli that typically colonize the flora of the human upper respiratory tract and have low pathogenic potential. There are limited case reports implicating the organisms as the cause of endocarditis, bacteremia, septic arthritis, ocular infection, and meningitis. In cases of keratitis and conjunctivitis, Moraxella nonliquefaciens is not commonly isolated from the ocular surface. We present a case of a diabetic patient who developed late-onset bleb-related endophthalmitis caused by M. nonliquefaciens 4 years after glaucoma filtering surgery. Within one day, the patient presented with an acutely fulminant course with sudden visual loss, redness, and ocular pain. Appropriate antibiotic treatment and early vitrectomy resulted in a favorable final visual acuity of 20/100, which was his vision prior to infection. The use of Matrix-Assisted Laser Desorption Ionization-Time of Flight Mass spectrometry (MALDI-TOF MS) enabled the rapid identification of the organism. Endophthalmitis caused by M. nonliquefaciens should be considered in patients who underwent glaucoma filtering surgery with antifibrotic agents.